PENGUKURAN KINERJA JURNAL ILMIAH TERAKREDITASI DI BATAN (ANALISIS BIBLIOMETRIK) - Noeraida Noeraida (Jurnal Pustakawan Indonesia, 2020)
Measurement of the performance of scientific journals needs to be done to evaluate and improve the quality, quantity and scientific impact of R&D practitioners. This study aims to evaluate the performance of accredited scientific journals in BATAN to improve the quality of journal management more optimally. The method used is bibliometric analysis. Data sources were obtained from the journal portal at http://jurnal.batan.go.id. Data processing and analysis using Microsoft Excel, Publish or Perish Software (PoP) and VOSviewer. The results of the study show that all journals have a good degree of scale. There are 4 journal titles that have not been indexed in DOAJ. The most productive writer is Wisnu Ari Adi, and the most cited are S. Hartanto and Ratnawati. Journal metric analysis results show the scientific impact measured by the number of articles cited included in the high category. The most productive and cited journal is J. Sains Materi Indonesia, but the journal that has the highest ratio of the number of cytities is Urania at 1,44. Visualization of collaboration shows the collaboration between authors obtained from eight accredited journals.